Gastric Medullary Carcinoma with Sporadic Mismatch Repair Deficiency and a TP53 R273C Mutation: An Unusual Case with Wild-Type BRAF - Brett M. Lowenthal; Theresa W. Chan; John A. Thorson; Kaitlyn J. Kelly; Thomas J. Savides; Mark A. Valasek (Hindawi Limited, 2017)
Medullary carcinoma has long been recognized as a subtype of colorectal cancer associated with microsatellite instability and Lynch syndrome. Gastric medullary carcinoma is a very rare neoplasm. We report a 67-year-old male who presented with a solitary gastric mass. Total gastrectomy revealed a well-demarcated, poorly differentiated carcinoma with an organoid growth pattern, pushing borders, and abundant peritumoral lymphocytic response. The prior cytology was cellular with immunohistochemical panel consistent with upper gastrointestinal/pancreaticobiliary origin. Overall, the histopathologic findings were consistent with gastric medullary carcinoma. A mismatch repair panel revealed a mismatch repair protein deficient tumor with loss of MLH1 and PMS2 expression. BRAF V600E immunostain (VE1) and BRAF molecular testing were negative, indicating a wild-type gene. Tumor sequencing of MLH1 demonstrated a wild-type gene, while our molecular panel identified TP53 c.817C>T (p.R273C) mutation. These findings were compatible with a sporadic tumor. Given that morphologically identical medullary tumors often occur in Lynch syndrome, it is possible that mismatch repair loss is an early event in sporadic tumors with p53 mutation being a late event. Despite having wild-type BRAF, this tumor is sporadic and unrelated to Lynch syndrome. This case report demonstrates that coordinate ancillary studies are needed to resolve sporadic versus hereditary rare tumors.